An integrated analysis of the comparison of regulations for the management and control of Legionella: Legal and experimental perspectives. - Serrano Huerta, Sara; Gómez Barbosa, María; Ruiz Salvador, Ángel Rabdel (Biosaia: Revista de los másteres de Biotecnología Sanitaria y Biotecnología Ambiental, Industrial y Alimentaria, 2024)
Legionella is a genus of bacteria that can be found in surface water all over the world, especially in water systems with little movement. This genus of bacteria causes the life-threatening disease legionellosis, which in its mildest form is called Pontiac fever. Legislation on the prevention and control of this microorganisms has been unchanged for many years, and recently (June 2022, implemented in January 2023) the Royal Decree regulating it has been modified. Royal Decree 487/2022 establishes the health requirements for the prevention and control of legionellosis, and repeals Royal Decree 865/2003. The aim of this work is to compare both laws, to find out how the procedures for the treatment of Legionella change, as well as to compare them with the current ISO standards and ministerial guides, and to analyse the royal decree and standards currently in force and the standards and procedures used in Laboratorios Vital. In the initial approaches of this study, gaps were found in the ISO standards (document that explains how to detect and analyse Legionella) that this work aims to fill. Among these gaps, we found that interrupted incubation is not considered as part of the possible procedures for Legionella. The results obtained to fill this gap in particular are the possibility of applying interrupted incubation for Legionella, as the tests carried out did not contemplate significant differences between samples with and without interrupted incubation.